Sustainable Household Organic Waste Management via Vermicomposting - S.H., Fauziah; P., Agamuthu (Malaysian Journal of Science, 2009)
Increasing waste generation in developing countries has alarmed authorities on waste disposal issues. Therefore, various alternatives have been looked into to reduce waste disposed into landfill. Among others are the bioremediation options which may allow the conversion of putrescible wastes into value added products such as compost, biogas and others. This study was aimed to find optimal experimental set-up to conduct small scale vermicomposting suitable for households, since approximately 40-50% (wt) of the waste is putrescible component. The wastes were weighed and exposed to worms namely Eisenia foetida. Results indicated that household putrescible waste can easily undergo vermicomposting. However, factors such as high acidity and presence of certain materials in the waste can be detrimental to this process. Worms are very sensitive to pH changes and the vermicomposting process will reduce drastically when pH is lower than 5.0. Experimental set-up with the layering system proved to be the best method of conducting small scale vermicomposting. The layering set-up prevents worms from escaping the vermicomposting system and allows the gathering of the offspring in a safe environment. Different combinations of organic mixture resulted with different rate of vermicomposting completion. The fastest to degrade was the combination of kitchen waste with vermicompost, which come to completion within three weeks. Vermicompost provides the most suitable environment for the worms to flourish in addition to the availability of less complex components in kitchen waste. The average water holding capacity of the vermicompost was 25% (wt) while the total organic content was 12%. In conclusion, vermicomposting of organic components found in the MSW stream can be accomplished by taking into consideration crucial factors such as acidity and presence of hindering components. The identification of the most suitable conditions for vermicomposting will allow the implementation of this alternative biological remedy to reduce waste and tackle the problem in waste management, particularly in developing countries. Pertambahan penghasilan sisa di negara-negara membangun membimbangkan pihak berkuasa. Maka, pelbagai alternatif telah dipertimbangkan untuk mengurangkan jumlah sisa ke tapak pelupusan. Antara pilihan yang ada ialah bioremediasi yang membolehkan pertukaran sisa yang mudah terurai kepada produk bernilai seperti kompos, biogas dan lain-lain. Kajian ini bertujuan untuk mengetahui penyediaan eksperimen terbaik bagi menjalankan proses vermi-pengkomposan skala kecil yang sesuai bagi isirumah memandangkan hampir 40-50% (berat) sisa yang dihasilkan terdiri daripada bahan mudah terurai. Sisa ditimbang dan didedahkan kepada cacing jenis Eisenia foetida. Keputusan menunjukkan bahawa sisa mudah terurai yang dihasilkan sesuai menjalani proses vermi-pengkomposan. Walau bagaimanapun, faktor- faktor seperti keasidan yang tinggi dan kehadiran elemen-elemen tertentu di dalam sisa boleh membantutkan proses ini. Cacing-cacing ini sensitif kepada perubahan pH dan proses vermi-pengkomposan akan menurun dengan drastik apabila pH kurang dari 5.0. Persediaan eksperimen dengan sistem lapisan terbukti sebagai teknik terbaik bagi menjalankan vermi-pengkomposan skala kecil. Sistem lapisan menghalang cacing keluar dari sistem vermi-pengkomposan dan membolehkan penggumpulan anak-anak cacing dalam persekitaran yang selamat. Kombinasi-kombinasi yang berbeza dalam campuran organik lengkap diproses pada kadar yang berbeza. Campuran sisa dapur dan vermi-kompos paling cepat terurai iaitu selepas tiga minggu. Ini adalah kerana ia menyediakan persekitaran yang paling sesuai bagi cacing untuk membiak di samping terdapatnya komponen-komponen yang kurang kompleks. Secara purata kapasiti air tanah bagi vermi-kompos ialah 25% sementara kandungan organik total ialah 12%. Sebagai kesimpulan, vermi-pengkomposan komponen organik dalam sisa munisipal boleh dijalankan dengan mengambil kira beberapa faktor penting seperti asiditi dan kehadiran komponen penghalang tertentu. Pengenalpastian keadaan yang paling sesuai bagi vermi- pengkomposan membolehkan perlaksanaan rawatan biologi alternatif ini untuk mengurangkan sisa dan menyelesaikan masalah pengurusan sisa terutama di negara-negara membangun.